IFRS for SMEs: eine interessante Option für deutsche KMUs auf dem Gebiet der Konzernrechnungslegung? - Klaus Henselmann; Benjamin Roos (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2009)
The paper analyzes whether the International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs), published July 9, 2009, could be an interesting option for the consolidated financial statements of small and medium-sized entities (SMEs) in Germany. Background is the intention of the IASB to give SMEs an attractive alternative in accounting according to international standards. For this reason the analysis includes a comparison of the sections of the IFRS for SMEs concerning consolidated financial statement accounting with Full-IFRS and the modernized German GAAP.
Keywords: G18; G38; K22; M41; M42; 650; Full-IFRS; IFRS for SMEs; Konzernrechnungslegung; Kleine und Mittlere Unternehmen (KMUs); nicht-kapitalmarktorientierte Unternehmen; Small and Medium-sized Entities